2003
DOI: 10.1046/j.1365-2036.2003.01455.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative pharmacokinetics and safety of lansoprazole oral capsules and orally disintegrating tablets in healthy subjects

Abstract: SUMMARYBackground: Many individuals with acid-related gastrointestinal disorders have difficulty in swallowing oral agents. Aim: To compare the bio-availability of a single dose of lansoprazole orally disintegrating tablet with that of an intact capsule. Methods: One hundred and twenty healthy subjects participated in two prospective, Phase I, open-label, two-period cross-over studies to receive lansoprazole, 15 mg or 30 mg. Within each study, subjects were randomized into two parallel cohorts consisting of 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 24 publications
3
34
0
Order By: Relevance
“…Indeed, PPIs are mainly metabolized by CYP2C19, and because the impact of CYP2C19 polymorphism on drug concentrations has been well established, different concentrations should be considered (Goldstein, 2001;Simon et al, 2011). A previous group described the maximum concentration of carriers of a loss of function allele in the plasma for omeprazole (3.1 mM), lansoprazole (4.9 mM), and pantoprazole (11.5 mM) according to the CYP2C19 "poor metabolizer" phenotype (Regardh et al, 1990;Pue et al, 1993;Yasuda et al, 1995;Ieiri et al, 2001;Freston et al, 2003). The plasma concentrations were lower in carriers of the normal allele with an "extensive metabolizer" phenotype, 1.6, 2.4, and 5.4 mM for omeprazole, lansoprazole, and pantoprazole, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, PPIs are mainly metabolized by CYP2C19, and because the impact of CYP2C19 polymorphism on drug concentrations has been well established, different concentrations should be considered (Goldstein, 2001;Simon et al, 2011). A previous group described the maximum concentration of carriers of a loss of function allele in the plasma for omeprazole (3.1 mM), lansoprazole (4.9 mM), and pantoprazole (11.5 mM) according to the CYP2C19 "poor metabolizer" phenotype (Regardh et al, 1990;Pue et al, 1993;Yasuda et al, 1995;Ieiri et al, 2001;Freston et al, 2003). The plasma concentrations were lower in carriers of the normal allele with an "extensive metabolizer" phenotype, 1.6, 2.4, and 5.4 mM for omeprazole, lansoprazole, and pantoprazole, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In two studies reported by Freston et al [18], the average disintegration times of LFDT without water were found to be 48 and 53 s for the 15- and 30-mg doses, respectively.…”
Section: Lansoprazole Orally Disintegrating Tabletmentioning
confidence: 97%
“…In two studies reported by Freston et al [18], the safety and bioavailability of LFDT taken without water were compared with lansoprazole capsules after a single dose of 15 or 30 mg. Each study enrolled 60 healthy adults and utilized a randomized, single-center, two-period, crossover design with a 7-day washout interval. The mean plasma concentration profiles were comparable for LFDT and lansoprazole capsules at both 15- and 30-mg doses (fig.…”
Section: Lansoprazole Orally Disintegrating Tabletmentioning
confidence: 99%
See 1 more Smart Citation
“…Newer formulations such as the lansoprazole fast oro-dispersible tablet do not need to be taken with water and are particularly useful in the elderly and those with swallowing difficulties. The lansoprazole preparation has been shown to be bio-equivalent to the conventional preparation and thus has the same efficacy for healing and maintenance therapy [43]. …”
Section: Therapeutic Optionsmentioning
confidence: 99%